2024
DOI: 10.2147/pgpm.s438978
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Mitochondrial tRNA Mutation in Chinese Family with Type 2 Diabetes Mellitus

Xing Li,
Jinyao Shang,
Shuang Li
et al.

Abstract: Background Mutations in mitochondrial tRNA (mt-tRNA) could be the origin of some type 2 diabetes mellitus (T2DM) cases, but the mechanism remained largely unknown. Aim The aim of this study was to assess the impact of a novel mitochondrial tRNA Cys /tRNA Tyr A5826G mutation on the development and progression of T2DM. Methods A four-generation Han Chinese family with maternally inherited di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…We read with interest the article by Li et al about a four-generation Chinese family with maternally-inherited diabetes due to the novel mtDNA variant m.5826A>G at the conjunction between tRNA(Cys) and tRNA(Tyr). 1 Cybrid cells carrying the variant m.5826A>G showed a 36% reduction in ATP production, a 22% reduction in mitochondrial membrane potential, and a 33% increase in ROS production compared to wild-type cells. 1 It was concluded that the m.5826A>G variant is pathogenic and presents as mitochondrial diabetes.…”
Section: Dear Editormentioning
confidence: 94%
See 4 more Smart Citations
“…We read with interest the article by Li et al about a four-generation Chinese family with maternally-inherited diabetes due to the novel mtDNA variant m.5826A>G at the conjunction between tRNA(Cys) and tRNA(Tyr). 1 Cybrid cells carrying the variant m.5826A>G showed a 36% reduction in ATP production, a 22% reduction in mitochondrial membrane potential, and a 33% increase in ROS production compared to wild-type cells. 1 It was concluded that the m.5826A>G variant is pathogenic and presents as mitochondrial diabetes.…”
Section: Dear Editormentioning
confidence: 94%
“… 1 Cybrid cells carrying the variant m.5826A>G showed a 36% reduction in ATP production, a 22% reduction in mitochondrial membrane potential, and a 33% increase in ROS production compared to wild-type cells. 1 It was concluded that the m.5826A>G variant is pathogenic and presents as mitochondrial diabetes. 1 The study is attractive but raises concerns that should be discussed.…”
Section: Dear Editormentioning
confidence: 94%
See 3 more Smart Citations